2017
DOI: 10.2217/nnm-2017-0143
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanocarrier for Drug and Gene Delivery Via Local Administration in Mucosal Tissues

Abstract: Local administration has many advantages for treating diseases. However, the surface mucus layer becomes a major obstacle that easily traps and fast removes local administrated drugs and genes in mucosal tissues. Fortunately, the rapidly developing nanocarriers with special physical and chemical properties may help to refine the treatment of mucosal tissues via delivering drugs and genes to the target tissue, and prolong the drug action time. Therefore, this review focuses on the strategies to apply different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 130 publications
0
22
0
Order By: Relevance
“…However, plenty of research has been conducted concerning PEI derivative applications for nucleic acid transference to the lung, but more attempts should be made for introducing new strategies based on cationic polymer vectors for more efficient gene delivery systems. [100][101][102] Recently, a novel carrier based on a poly(L-lysine) (PLL)-alkyl-PEI copolymer was designed and the effect of aptamer conjugation on short hairpin RNA (shRNA) plasmid gene delivery efficiency was investigated for gene delivery of this modified vector to lung cancer cells. Beside PEI, PLL is a cationic polymer non-viral vector that can be used for most gene delivery purposes.…”
Section: Targeted Gene Delivery By Aptamer-pei Nanocomplexesmentioning
confidence: 99%
“…However, plenty of research has been conducted concerning PEI derivative applications for nucleic acid transference to the lung, but more attempts should be made for introducing new strategies based on cationic polymer vectors for more efficient gene delivery systems. [100][101][102] Recently, a novel carrier based on a poly(L-lysine) (PLL)-alkyl-PEI copolymer was designed and the effect of aptamer conjugation on short hairpin RNA (shRNA) plasmid gene delivery efficiency was investigated for gene delivery of this modified vector to lung cancer cells. Beside PEI, PLL is a cationic polymer non-viral vector that can be used for most gene delivery purposes.…”
Section: Targeted Gene Delivery By Aptamer-pei Nanocomplexesmentioning
confidence: 99%
“…Both coated and uncoated PHA films were observed to demonstrate a biocompatible behavior in post histological evaluation, though a more aligned spread of the marker was detected in the PHA/PD samples. Finally, for localized and controlled delivery, it is necessary to prolong and advance the contact between the drug and the mucosal lesion ( Colley et al, 2018 ; Wang et al, 2018 ); this involves improving surface free energy as well as wettability. In this study, a PD coating was shown to be a powerful route in converting a bioinert substrate into a reasonably bioactive one; whereby the hydrophilicity of the polymer surface was improved, and a higher surface energy value was exhibited accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, more nano‐drugs delivery systems have been developed; however, the mucoadhesion between nanoparticles and mucus make them incapable of reaching the underlying epithelium or subepithelial tissues, which has limited their application . To date, although there are numerous studies on mucoadhesive nanoparticles to improve the drug permeability through mucosal surfaces, the effect is limited.…”
Section: Biomedical Materials Based On Cysteine and Its Derivativesmentioning
confidence: 99%